Marine natural products as an important source of bioactive substances for non-alcoholic fatty liver disease management - Menglei Shi; Menglei Shi; Sisi Chen; Sisi Chen; Yutong Feng; Yutong Feng; Shiyuan Wang; Yuyu Xia; Jianlin He (Frontiers in Marine Science)
With an estimated global prevalence of 32.4%, non-alcoholic fatty liver disease (NAFLD) is currently the most prevalent chronic liver condition. The marine ecosystem, distinguished by its distinctive environmental characteristics, is a treasure trove of novel lead compounds possessing unique chemical structures, offering promising avenues for the development of new therapeutic agents or dietary supplement targeting NAFLD. Marine bioactive substances from natural products, such as polysaccharides, polyphenols, polyunsaturated fatty acids, and peptides, have been shown to benefit liver health by alleviating metabolic dysfunction through multiple mechanisms. This paper reviews the effects of marine bioactive substances from various marine entities, including marine fauna, flora, and microorganisms, on the regulation of NAFLD. A brief overview of the predominant pathogenic mechanisms underlying the disease is also provided, thereby establishing a critical link between the therapeutic potential of marine bioactive substances and the management of NAFLD.